The Effect of Individual and Group Competitive Teaching Strategies on Learning Gymnastics Skills by Female Students at Al-Bayet University - Maysloon Alshadedh (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
The study aims to examine the effect of individual and group competitive teaching strategies of female students learning some gymnastics skills at the department of physical education. The researcher adopted a semi-experimental study design. The study sample consisted of (30) female students enrolled in a gymnastics (1) course. These students were randomly assigned into (3) even study groups, each consisting of (10) students. The first was controlled and taught using the conventional teaching method. The second represented the first experimental group and was taught using the individual competitive teaching strategy while the third group represented the second experimental group and was taught using the team competitive teaching strategy. The results of the study showed statistically significant differences (α ≤ 0.05) between the pre-posttest means scores for the three study groups, in favor of the post-test means scores. There were also statistically significant differences (α ≤ 0.05) in the post-test means scores between the control group and the two experimental groups, in favor of the two experimental groups in learning some gymnastics skills. The study recommended the use of different teaching strategies such as individual and team competitive teaching strategies when teaching gymnastics skills and not solely relying on conventional teaching methods when teaching gymnastics to improve individual performance.